A study of the factors influencing HIV-preventive intentions among “hookup” application users - Li, Mengyu; Li, Ning (Frontiers in Psychology, 2023)
“Hooking up” with strangers is the act of experiencing sexual intimacy without an investment in a romantic relationship. Social media provide more convenient conditions for hooking up; however, it also poses a greater risk for HIV infection. Therefore, it is necessary to study the factors influencing the HIV prevention intentions of those who engage in online dating to identify effective strategies for preventing the spread of HIV. This study consists of a questionnaire survey targeting 520 users of the application Hello Group, and the survey results revealed that structural equation modeling is a useful framework for understanding the risk of HIV transmission in casual hookup encounters. In addition, the combination of the health belief model and the theory of planned behavior can provide suggestions for enhancing users’ HIV prevention intentions. The results showed that mindfulness, the Chinese cultural context, perceived benefits, and self-efficacy were the main predictors of users’ HIV protection intention when using online dating applications. Among the perceived HIV risks when online dating, only perceived barriers had a negative effect on users’ HIV prevention intentions. In addition, attitude, subjective norms, and behavior control acted as mediating variables between independent variables and HIV protection intention; however, the mediating effect of attitude on perceived benefits and intentions was not significant. According to our study, some users misunderstand risks and make incorrect assessments of the cultural risks of hooking up. Therefore, it is necessary to pay attention to research on the psychological tendencies of users and risk intervention when engaging in the act of hooking up.